Highly regioselective complexation of tungsten with Eu@C82/Eu@C84: interplay between endohedral and exohedral metallic units induced by electron transfer. Issue 19 (3rd May 2019) - Bao, Lipiao; Yu, Pengyuan; Li, Ying; Pan, Changwang; Shen, Wangqiang; Jin, Peng; Liang, Shuquan; Lu, Xing
Abstract : Interplay between inner and outer metallic units induced by charge transfer is observed in tungsten complexes of Eu@ C 2 (5)-C82 and Eu@ C 2 (13)-C84 . Abstract : Interactions between the inner and outer units through a fullerene cage are of fundamental importance for the creation of molecular spintronics and machines, but the mechanism of such through-cage interplay is still unclear. In this work, we have designed and synthesized two prototypical compounds which contain only a single europium atom inside the cage and merely a tungsten atom coordinating outside to clarify the interactions between the endohedral and exohedral metallic units. They are obtained by reacting a tungsten complex W(CO)4 (Ph2 PC2 H4 PPh2 ) (1 ) with the corresponding metallofullerenes in a highly regioselective manner (2a for Eu@ C 2 (5)-C82 and2b for Eu@ C 2 (13)-C84 ). On the one hand, the endohedral Eu-doping has changed the LUMO distribution on C 2 (5)-C82 / C 2 (13)-C84 dramatically, via electron transfer, which governs the addition pattern of the exohedral tungsten resulting in surprisingly high regioselectivity. On the other hand, the exohedral tungsten coordination with Eu@ C 2 (5)-C82/ Eu@ C 2 (13)-C84 has restricted the motion of the internal europium ion to some extent by changing the electrostatic potentials, as confirmed by the X-ray results of2a, 2b and the corresponding pristine metallofullerenes cocrystallized with Ni(OEP) (OEP is the dianion of octaethylporphyrin). We now make it clear that the interplay between the endohedral and exohedral metallic units can be realized in a single system by means of intramolecular charge transfer, which may arouse interest in the design and utilization of novel metallofullerene-based molecular devices.